2015
DOI: 10.1128/aem.01566-15
|View full text |Cite
|
Sign up to set email alerts
|

A Gnotobiotic Pig Model for Determining Human Norovirus Inactivation by High-Pressure Processing

Abstract: e Human norovirus (NoV) is responsible for over 90% of outbreaks of acute nonbacterial gastroenteritis worldwide and accounts for 60% of cases of foodborne illness in the United States. Currently, the infectivity of human NoVs is poorly understood due to the lack of a cell culture system. In this study, we determined the survival of a human NoV genogroup II, genotype 4 (GII.4) strain in seeded oyster homogenates after high-pressure processing (HPP) using a novel receptor binding assay and a gnotobiotic pig mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…This is in agreement with the findings of Leon et al (44) and indicates that the PGM-MB binding assay may provide information on the potential infectivity of NoV detectable by RT-PCR. A recent study by Lou et al (56) showed that HPP treatment of NoV-contaminated oysters, which were subsequently fed to gnotobiotic piglets, gave infectivity results consistent with those predicted from the PGM-MB binding assay. Ye et al (110) refined this detection system by incorporating treatment with RNase prior to binding to the mucin, to remove RNA from damaged virus capsids.…”
Section: Hhpsupporting
confidence: 55%
See 1 more Smart Citation
“…This is in agreement with the findings of Leon et al (44) and indicates that the PGM-MB binding assay may provide information on the potential infectivity of NoV detectable by RT-PCR. A recent study by Lou et al (56) showed that HPP treatment of NoV-contaminated oysters, which were subsequently fed to gnotobiotic piglets, gave infectivity results consistent with those predicted from the PGM-MB binding assay. Ye et al (110) refined this detection system by incorporating treatment with RNase prior to binding to the mucin, to remove RNA from damaged virus capsids.…”
Section: Hhpsupporting
confidence: 55%
“…This work is undergoing validation to ascertain its efficacy and could provide a better indication for the presence of infectious NoV particles using RT-qPCR. The PGM-MB binding assay gave good predictive ability to differentiate infectious viruses when compared to an infectivity study of NoV infection in a gnotobiotic pig model (56). Capsid integrity has also been evaluated using propidium monoazide intercalation and RNase treatment (21), virus binding to Caco-2 cells followed by long-range RT-qPCR (47), and other techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the treatment temperature generally ended up enhancing MNV inactivation, as reducing the temperature from 20 to 0 • C increased viral reduction by nearly 4 log 10 when a 350 MPa 2 min treatment was applied (Huang et al, 2014), similar to the observations for human norovirus strains (Lou et al, 2015b. Additionally, introducing water to the samples prior to treatment also significantly enhanced reduction, achieving additional 1-2 log reduction over the "dry" sample.…”
Section: High Pressure Processingsupporting
confidence: 65%
“…However, when the pressure was increased above 800 MPa complete reduction of VLP integrity was observed in 15 min or less . Interestingly, further human norovirus work for which infectivity was determined using a gnotobiotic pig model demonstrated the efficacy of HPP with treatments as low as 350 MPa for 2 min so long as treatments were at 0 • C (Lou et al, 2015b).…”
Section: High Pressure Processingmentioning
confidence: 99%
“…HEV response to 500 MPa for 15 min has been previously investigated with RT-qPCR viability markers (PMAxx and platinum chloride, PtCl4-RT-qPCR), but was only able to report the presence of intact viral particles post treatment (43). The inactivation by HPP of other foodborne viruses, including norovirus, Hepatitis A virus (HAV), and surrogates for foodborne viruses has been investigated (26, 44-46). The sensitivity of specific viruses to high-pressure treatment can vary significantly.…”
Section: Discussionmentioning
confidence: 99%